Stimulation of Cortico-Subthalamic Projections Amplifies Resting Motor Circuit Activity and Leads to Increased Locomotion in Dopamine-Depleted Mice - Sanders, Teresa H. (Frontiers in Integrative Neuroscience, 2017)
Deep brain stimulation (DBS) of the subthalamic nucleus (STN) improves motor function in patients with Parkinson's disease (PD). STN-DBS enables similar improved motor function, including increased movement speed (reduced bradykinesia), in the 6-OHDA dopamine-depletion mouse model of PD. Previous analyses of electrophysiological recordings from STN and motor cortex (M1) have explored signaling changes that correspond to PD and amelioration of PD symptoms. The most common results show an increase in beta frequency power during 'off' states and a reduction in beta during ‘on’ states. Surprisingly, however, few studies have analyzed whole signal measures of amplitude and coherence during stimulation in freely moving subjects. In previous work by the author, specific transfection of layer 5 motor cortex projections to the STN revealed an axonal network with collaterals reaching to multiple non-dopaminergic subcortical areas of the brain. The large excitatory shift that stimulation of this axonal network could potentially induce inspired the current study's hypothesis that amplification of excitatory signaling occurs during stimulation of cortico-subthalamic projections. The results show that, in awake mice, 1) the root-mean-square amplitudes of STN and M1 local field potentials (LFPs) are significantly decreased ipsilateral to chronic unilateral 6-OHDA lesions, 2) stimulation of cortico-subthalamic projections increases the amplitude of M1- and STN-LFPs, and 3) M1-LFP amplitude correlates strongly with locomotion speed in lesioned mice. Together, these findings demonstrate that bradykinesia-reducing stimulation of cortico-subthalamic projections amplifies both cortical and subcortical motor circuit activity in unilaterally dopamine-depleted mice. Most PD treatments are focused on increasing dopamine in the dorsal striatum. However, in this study, stimulation of layer 5 cortico-subthalamic glutamatergic axons that do not directly project to dopaminergic neurons increased movement and amplified cortico-subthalamic excitatory signaling in dopamine-depleted mice. The correlation between M1-LFP amplitude and locomotion speed observed in these mice points to a role for upregulated hyperdirect pathway excitatory signaling in bradykinesia amelioration. In addition to providing insight into the elusive mechanisms of DBS, these motor circuit amplification relationships suggest that specific manipulation of NMDA, AMPA, and/or metabotropic glutamate receptors in the hyperdirect pathway may be beneficial for upregulating signaling and movement in PD.